2020
DOI: 10.1111/1759-7714.13358
|View full text |Cite
|
Sign up to set email alerts
|

TRIAP1 knockdown sensitizes non‐small cell lung cancer to ionizing radiation by disrupting redox homeostasis

Abstract: Background Radioresistance of some non‐small cell lung cancer (NSCLC) types increases the risk of recurrence or metastasis in afflicted patients, following radiotherapy. As such, further improvements to NSCLC radiotherapy are needed. The expression of oncogene TP53‐regulated inhibitor of apoptosis 1 (TRIAP1) in NSCLC is increased following irradiation. Furthermore, gene set enrichment analysis (GSEA) has suggested that TRIAP1 might be involved in maintaining redox homeostasis. This in turn might enhance cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…These results suggest that the TMX1-NFAT1 axis promotes cancer progression, and elevated TMX1 expression is indicative of cancer aggressiveness and poor survival outcome. TP53-regulated inhibitor of apoptosis 1 (TRIAP1), an oncogenic protein highly expressed in lung adenocarcinoma, has been shown to mediate the upregulation of some anti-oxidative proteins, including TMX1 and TMX2 (29). The expression levels of TMX1 and TMX2 were inversely correlated with overall survival of the patients.…”
Section: Cancermentioning
confidence: 99%
“…These results suggest that the TMX1-NFAT1 axis promotes cancer progression, and elevated TMX1 expression is indicative of cancer aggressiveness and poor survival outcome. TP53-regulated inhibitor of apoptosis 1 (TRIAP1), an oncogenic protein highly expressed in lung adenocarcinoma, has been shown to mediate the upregulation of some anti-oxidative proteins, including TMX1 and TMX2 (29). The expression levels of TMX1 and TMX2 were inversely correlated with overall survival of the patients.…”
Section: Cancermentioning
confidence: 99%
“…Studies have shown that TRIAP1 is involved in the occurrence of a variety of tumours, such as myeloma, ovarian cancer, and nasopharyngeal carcinoma [14][15][16][17]. High expression of TRIAP1 in tumours often indicates poor prognosis for patients [18,19]. A previous study has reported that the decrease in TRIAP1 expression is related to the enhancement of chemosensitivity in osteosarcoma [20].…”
Section: Page 3/13mentioning
confidence: 99%
“…Studies have shown that TRIAP1 is involved in the occurrence of a variety of tumours, such as myeloma, ovarian cancer, and nasopharyngeal carcinoma [ 14 17 ]. High expression of TRIAP1 in tumours often indicates poor prognosis for patients [ 18 , 19 ]. A previous study has reported that the decrease in TRIAP1 expression is related to the enhancement of chemosensitivity in osteosarcoma [ 20 ].…”
Section: Introductionmentioning
confidence: 99%